Glucose-6-Phosphate Dehydrogenase Deficiency in Icteric Neonates with indirect Hyperbilirubinemia (Medical Forum Monthly, 2020)
Objective: Determining the Glucose-6-phosphate dehydrogenase (G6PD) deficiency in icteric neonates with indirect hyperbilirubinemia reporting at a tertiary care hospital of Sindh.Study Design: Cross Sectional study.Place and Duration of Study: This study was conducted at the Department of Paediatrics, SMBB Medical College Layari General Hospital, Karachi, Sindh from January 2017 to May 2019.Materials and Methods: A sample of 311 icteric neonates was selected by convenient probability sampling through inclusion and exclusion criteria. Complete blood counts and reticulocyte counts were analyzed on Sysmex KX-21 hematology analyzer. Serum bilirubin and glucose- 6-phosphate dehydrogenase were estimated by diazo method and color decolorization method (Sigma assay kit). Statistical analysis was performed at 95% confidence interval (P≤ 0.05) using SPSS software 21.0 (IBM, Inc USA).Results: Of 311 sample size, 23 (7.39%) revealed G6PD deficiency and 288 (92.6%) neonates revealed normal G6PD concentrations. Age, Gestational age and hemoglobin were similar in both G6PD normal and deficient neonates. Anemia, reticulocyte counts, direct, indirect and total bilirubin revealed significant differences in G6PD deficient and normal neonates (P=0.0001).Conclusion: The present study reports 7.39% frequency of Glucose-6-phosphate dehydrogenase deficiency in icteric neonates with indirect hyperbilirubinemia.